Astrocytic Propagation of Tau in the Context of Alzheimer's Disease - Fleeman, Rebecca M.; Proctor, Elizabeth A. (Frontiers in Cellular Neuroscience, 2021)
More than 5.5 million Americans are currently living with Alzheimer’s disease (AD), and the incidence is growing rapidly with our aging population. Numerous therapeutics have failed to make it to the clinic, potentially due to a focus on presumptive pathogenic proteins instead of cell-type-specific signaling mechanisms. The tau propagation hypothesis that inter-neuronal tau transfer drives AD pathology has recently garnered attention, as accumulation of pathological tau in the brain has high clinical significance in correlating with progression of cognitive AD symptoms. However, studies on tau pathology in AD are classically neuron-centric and have greatly overlooked cell-type specific effects of tau internalization, degradation, and propagation. While the contribution of microglia to tau processing and propagation is beginning to be recognized and understood, astrocytes, glial cells in the brain important for maintaining neuronal metabolic, synaptic, trophic, and immune function which can produce, internalize, degrade, and propagate tau are understudied in their ability to affect AD progression through tau pathology. Here, we showcase evidence for whether tau uptake by astrocytes may be beneficial or detrimental to neuronal health and how astrocytes and their immunometabolic functions may be key targets for future successful AD therapies.